Determining market concentration - Ginevičius, Romualdas (Journal of Business Economics and Management, 2007)
One of the major problems associated with market concentration is its quantitative evaluation. In fact, a concept of the concentration curve is used in almost every case. The suggested measures may be classified as discrete or accumulative values. All of them are of limited accuracy because the first ones take into account only a part of the concentration curve, while the second values cannot adequately describe the situation in the market. The accuracy of the above measures can be determined based on the total difference in the relationship between the carriers of particular attributes in the market and the value calculated for them by the market concentration formula based on the suggested measure. The above measure yields the best result in determining the total difference.First Published Online: 14 Oct 2010